FRI0254 Predictive Factors for the Response to Infliximab Therapy in Patients with Behçet's Disease. (9th June 2015) - D'Angelo, S.; Leccese, P.; Padula, A.; Nigro, A.; Gilio, M.; Carriero, A.; Palazzi, C.; Olivieri, I.
Abstract : Background: Therapeutic approach of Behçet's disease (BD) depends on the clinical presentation and organ involved. The conventional immunosuppressive therapy is still the first approach to the treatment of disease and is aimed to improve the quality of life and prevent irreversible organ damage. However a variable percentage of patients with BD do not respond to traditional immunosuppressive agents or withdraw from treatment due to inefficacy or adverse events. Objectives: To identify the clinical factors predicting a good clinical response to Infliximab (IFX) therapy after 12 months in patients BD refractory to conventional therapy. Methods: Patients receiving IFX (5 mg/kg intravenously at weeks 0, 2, 6, and every 6-8 weeks subsequently) for BD unresponsive to conventional therapy (corticosteroids plus at least two different immunosuppressive drugs) were prospectively included. Clinical response to IFX therapy was based on the expert opinion and was graded as follows: remission, response, no response and worsening. Remission was defined as the complete disappearance of symptoms and signs of inflammation and response as at least 50% of improvement. Univariate and multivariate analyses were performed to identify factors associated with IFX good response (remission, response) at 12 months. Logistic regression analysis was performed to analyse which of the following measures at the start of treatment were associated with a good response: sex; age; disease duration; HLA-B51 status; indication for IFX treatment including uveitis, CNS involvement, severe mucocutaneous manifestations or others including arthritis, intestinal and vascular involvement; concomitant drugs including steroids (Ster), colchicine (Col), azathioprine (AZA) or cyclosporine (CSA). Results: The study included 73 BD patients (47 M/26 F; mean age 33.6±10.7 yrs; mean disease duration 12.3±9.3 yrs; 71.2% HLA-B51 positive). Indication for IFX treatment were uveitis in 38 patients, severe mucocutaneous manifestations in 13, CNS involvement in 16, intestinal involvement in 2, arthritis in 2, vascular involvement in the remaining 2.At 12 months, 56 patients (76.7%) had a good response to IFX, 4 (5.5%) patients had stopped for adverse events, and 13 (17.8%) had stopped for primary or secondary inefficacy. In the univariate analysis concomitant use of AZA (95.8% vs 67.3%, p<0.01) was the only factor associated with a good response. In a multivariate logistic regression analysis concomitant use of AZA was independently associated with a good therapeutic response (OR =34.2; 95% CI 2.7-435.8; p=0.007). None of the other variables analysed predicted response to treatment. Conclusions: This study has, for the first time, shown that concomitant use of AZA at the start of IFX treatment is a factor that seems to influence the probability of achieving a good therapeutic response in patients with refractory BD. Further support from larger studies is necessary so as to optimize the management of BD patients treated with IFX. Disclosure of Interest: None declared